The crime of massive and habitual capturing of money in Colombian criminal law (Article 316 of the Colombian Criminal Code) (2017)
This article has the aim to identify, starting from the respect of the principle of harm - nulla lex poenalis sine iniuria-, which is the legal interest protected by the article 316 of the Colombian Penal Code, which punishes the collection of public fund